The role of pediatricians in the diagnosis and management of IgE-mediated food allergy: a review - Gupta, Ruchi S.; Epstein, Ellen; Wood, Robert A. (Frontiers in Pediatrics, 2024)
Importance: Food allergy can often cause a significant burden on patients, families, and healthcare systems. The complexity of food allergy management requires a multidisciplinary approach involving different types of healthcare providers, including allergists, dieticians, psychologists, nurses, family practitioners and, of particular relevance for this article, pediatric primary caretakers. Pediatricians may be the first-line healthcare providers for food allergy: strategies for management and guideline adherence have been highlighted. Observations: This review article summarizes the up-to-date recommendations on the role of pediatricians in the diagnosis, management, and prevention of IgE-mediated food allergy. Early introduction of allergenic foods like peanut is known to be of importance to reduce the development of peanut allergy in infants, and pediatricians are essential for educating and supporting parents in this decision. In scenarios of limited allergist availability, as is often the case among rural, Medicaid and minority populations, pediatricians can assist in the evaluation and management of food allergy, and provide action plans, education and counselling for patients and families. Conclusions and relevance: Pediatric primary caretakers play a key role in the diagnosis, management, and prevention of IgE-mediated food allergy. As more diagnostic tools and therapies in food allergy become available, the need for a multidisciplinary team is paramount to optimize patient care.